The effects of dismissal protection on the hazard of remaining employed - Christine Lücke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Dismissal protection has experienced many statutory changes in Germany in the past decades. This paper estimates the effects of dismissal protection on the hazard of leaving the establishment using as identification that workers employed before the legal amendment maintained their previous dismissal protection. Utilizing linked employer-employee data (LIAB), the results hint to a higher hazard during the first six month of seniority and a smaller hazard thereafter if dismissal protection is granted. I do not find evidence for a positive effect of dismissal protection on matching quality.
Keywords: J68; J63; J23; 330